Johnston, Lynda (2019). Transforming gender, sex and place: Gender variant geographies - Ortiz Guitart, Anna (Documents d’Anàlisi Geogràfica, 2019)
Johnston, Lynda (2019) Transforming gender, sex and place: Gender variant geographies Oxon i Nova York: Routledge, 191 p. ISBN 9781472454799